Measuring Organizational Cultural Competence to Promote Diversity in Academic Healthcare Organizations - Jaya Aysola; Jaya Aysola; Jaya Aysola; Jaya Aysola; Diana Harris; Hairong Huo; Charmaine S. Wright; Eve Higginbotham; Eve Higginbotham (Mary Ann Liebert, 2018)
Purpose: To evaluate what drives respondent perceptions of health system organizational cultural competence. Methods: We estimated associations between survey respondent (n=3506) demographic characteristics, length of employment, position, and place of work and their reported perceptions of institutional culture. Results: In adjusted analyses, respondents self-identifying as non-Hispanic black versus non-Hispanic whites, females versus males, and lesbian/gay/bisexual/transgender/queer versus heterosexuals were significantly less likely to rank the cultural competence of their organization above average. Conclusion: Minorities and women were less likely to rank their organization as culturally competent. Organizational efforts to achieve cultural competency would benefit from measuring this factor to target their efforts.